Surgical outcome of pediatric intestinal obstruction in Amhara comprehensive specialized hospitals, September 2024 - Alazar Tamirat; Jemberu Nigussie; Gebeyaw Biset (BMC Surgery)
Abstract Background Intestinal obstruction is the most common acute abdominal disorders in children requiring emergency surgical management. Although surgical management remained the best treatment modality for intestinal obstruction, significant subset of children undergoing surgical management experiences unfavorable management outcomes. Unfavorable surgical management outcomes pose substantial impacts in children, their families, and the society. However, there has been limited evidence regarding the surgical management outcomes of intestinal obstruction among children in developing countries lie Ethiopia. Objective This study aims to assess surgical management outcomes of intestinal obstruction and its associated factors among children aged less than 15 years in eastern Amhara comprehensive specialized hospitals. Methods Institutional-based cross-sectional study design was employed among 262 children aged less than 15 years. The study participants were selected by simple random sampling techniques after proportional allocation of the sample to the study hospitals. Data was collected using a pretested data collection checklist and it was entered to Epi Data version 4.2 and analyzed using SPSS version 25 software. Variables with p-value of < 0.25 in the bi-variable analysis were entered into multi-variable logistic regression analyses. Finally, variables with p-value < 0.05 were declared to have a significant association with the outcome variable. Result Two hundred and sixty-two (262) children were included with a response rate of 100%. The finding reveals that nearly one third of children undergoing surgical management for intestinal obstruction (32.1%, 95% CI 26.3, 37.8) experienced unfavorable surgical management outcomes. The study indicated that gangrenous bowel (AOR:4.47, 95%CI:1.8, 11.1), malnutrition (AOR:4.16, 95% CI:1.77, 9.81), length of hospital stays > 7 days (AOR:3.89, 95% CI:1.69, 8.95), delay of surgery > 24 h (AOR:3.27, 95% CI:1.27, 8.42), and duration of surgery > 2 h (AOR:2.61, 95%CI:1.16, 5.88) were the risk factors for unfavorable surgical management outcome of intestinal obstruction. Conclusion The magnitude of unfavorable surgical outcome is higher than the expected rate nearly one in three children experience unfavorable surgical management outcome following surgical management of intestinal obstruction. The risk factors identified are mainly preventable which includes gangrenous bowel, malnutrition, prolonged hospital stay, delayed surgery after admission, and prolonged duration of surgery. Early identification and treatment of intestinal obstruction is recommended. In addition, implementation of standardized pre and postoperative care protocols will be needed to achieve favorable surgical management outcome.